2015
DOI: 10.1310/sci2104-294
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Electrical Stimulation–Induced Resistance Training After SCI: A Review of the Dudley Protocol

Abstract: Background: Neuromuscular electrical stimulation (NMES), often referred to as functional electrical stimulation (FES), has been used to activate paralyzed skeletal muscle in people with spinal cord injury (SCI). The goal of NMES has been to reverse some of the dramatic losses in skeletal muscle mass, to stimulate functional improvements in people with incomplete paralysis, and to produce some of the health benefits associated with exercise. Objective: The purpose of this brief review is to describe a quantifia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…Different protocols of functional electrical stimulation mimic different types of exercise (Fornusek and Davis ; Bickel et al. ). Both endurance and resistance training lead to an increase in satellite cell number, while resistance training also leads to an increase in myonuclear number (Bruusgaard et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different protocols of functional electrical stimulation mimic different types of exercise (Fornusek and Davis ; Bickel et al. ). Both endurance and resistance training lead to an increase in satellite cell number, while resistance training also leads to an increase in myonuclear number (Bruusgaard et al.…”
Section: Discussionmentioning
confidence: 99%
“…Electrical stimulation coupled with exercise improves the metabolic characteristics of skeletal muscle in spinal cord-injured individuals (Hjeltnes et al 1998;Gorgey et al 2017) and may be used as a potential activator of skeletal muscle regenerative machinery (Kern and Carraro 2014). Different protocols of functional electrical stimulation mimic different types of exercise (Fornusek and Davis 2008;Bickel et al 2015). Both endurance and resistance training lead to an increase in satellite cell number, while resistance training also leads to an increase in myonuclear number (Bruusgaard et al 2010;Kurosaka et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Electrically evoked resistance training (RT) using surface neuromuscular electrical stimulation (NMES), (Dudley's protocol), has proven to be an effective intervention to evoke muscle hypertrophy in persons with SCI. [7][8][9][10][11][12] Several studies indicated that RT, twice weekly from 8 to 16 weeks, increased muscle size significantly compared to pretraining cross-sectional areas (CSAs). [7][8][9][10][11][12] Dudley et al 7 showed that 8 weeks of twice-weekly NMES-RT restored knee extensor muscle size to 75% of what it was 6 weeks post-SCI.…”
Section: Introductionmentioning
confidence: 99%
“…Neuromuscular electrical stimulation (NMES) has been used extensively in rehabilitation settings, and numerous studies have demonstrated its efficacy in promoting adaptive responses in SCI patients. For example, NMES resistance exercise training induces skeletal muscle hypertrophy and may reduce IMF . A previous study reported that resistance NMES training also resulted in significant improvements in in‐vivo skeletal muscle oxidative capacity .…”
mentioning
confidence: 99%
“…For example, NMES resistance exercise training induces skeletal muscle hypertrophy and may reduce IMF. [20][21][22][23] A previous study reported that resistance NMES training also resulted in significant improvements in in-vivo skeletal muscle oxidative capacity. 24 These improvements averaged 25% and, although significant, were not enough to bring skeletal muscle oxidative capacity to near able-bodied levels.…”
mentioning
confidence: 99%